2005
DOI: 10.1177/1054773805275287
|View full text |Cite
|
Sign up to set email alerts
|

Survivor Preferences for Response to IPV Disclosure

Abstract: Intimate partner violence (IPV) is a major cause of health conditions among women presenting for health care. Many physicians and nurses miss potential opportunities to increase battered women's safety. The purpose of this study is to increase health care providers' understanding of abused women's preferences concerning provider response when they do disclose IPV in order to increase effectiveness of interventions. A total of 26 abused women from a larger study participated in five focus groups at three agenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 34 publications
4
49
0
1
Order By: Relevance
“…Hathaway, Willis & Zimmer, 2002). Similar to the women in our sample, the women in the USA also value medical proof, such as photographs of injuries taken by HCPs, that helps them establish credible testimony against their perpetrators in a court of law (Dienemann, Glass & Hyman, 2005). Another study conducted in the USA indicated that battered women also value information from HCPs on community resources, such as IPV programs (Zink, Jacobson, Regan & Pabst, 2004).…”
Section: Discussionmentioning
confidence: 62%
“…Hathaway, Willis & Zimmer, 2002). Similar to the women in our sample, the women in the USA also value medical proof, such as photographs of injuries taken by HCPs, that helps them establish credible testimony against their perpetrators in a court of law (Dienemann, Glass & Hyman, 2005). Another study conducted in the USA indicated that battered women also value information from HCPs on community resources, such as IPV programs (Zink, Jacobson, Regan & Pabst, 2004).…”
Section: Discussionmentioning
confidence: 62%
“…As in our study, the importance of a good physician-patient relationship for disclosure of violence is emphasized in most studies of female victims (Chang et al, 2005;Dienemann et al, 2005;Feder et al, 2006b) and is suggested to be more important than the actual wording of questions (Fogarty, Burge and McCord, 2002). Hence the relevance of only testing different wordings of questions or the mode of screening (face-to-face, written, computer based) as is sometimes done in research (Fogarty et al, 2002;MacMillan, Wathen, Jamieson et al, 2006;McCord-Duncan, Floyd, Kemp et al, 2006;Chen, Rovi, Washington et al, 2007) can be questioned .…”
Section: Health Care System's Response To Victims Of Interpersonal VImentioning
confidence: 84%
“…A wish for a supportive and individually tailored meeting with health care professionals was expressed by the men in study IV, which has also been expressed by female victims of intimate partner violence (Dienemann et al, 2005;Feder, Hutson, Ramsay and Taket, 2006b). As in our study, the importance of a good physician-patient relationship for disclosure of violence is emphasized in most studies of female victims (Chang et al, 2005;Dienemann et al, 2005;Feder et al, 2006b) and is suggested to be more important than the actual wording of questions (Fogarty, Burge and McCord, 2002).…”
Section: Health Care System's Response To Victims Of Interpersonal VImentioning
confidence: 99%
See 1 more Smart Citation
“…However, this crucial first step is influenced by a myriad of intrapersonal, interpersonal, and sociocultural factors, such as self-doubt and denial; discounting, minimizing, and victim blaming by the perpetrator; and societal attitudes that "normalize" or, conversely, "stigmatize" IPV (Dienemann, Glass, & Hyman, 2005). It is reasonable to assume that for women with disabilities, the confluence of these factors may present barriers in taking this first step.…”
Section: Disclosure Of Intimate Partner Violencementioning
confidence: 99%